PENGENDALIAN BIAYA DAN JADUAL TERPADU PADA PROYEK KONSTRUKSI - Ahmad Ridwan; Rekso Ajiono (Kadiri University, 2017)
The main resources limited to the stage of implementing a construction project are cost, quality and time. Planning, scheduling and controlling are important steps to take in order to achieve the project's objectives with limited resources. The